Taller de Gerencia de Proyectos - IS241 - 202101 - Mamani Anchea, Luis Camilo (2021)
Description: One of the challenges faced by organizations is how to transform proposals into practical actions and making sure that these results are achieved in time and with the available resources. This course presents concepts and tools that can be applied in project management and that can generate a substantial change to reach the proposed objectives. The contents of the course are aligned with the guidelines and standards of good project management practices presented in the Project Management Body of Knowledge (PMBOK¿) by the Project Management Institute (PMI). Purpose: The Project Management Workshop course will be taught in English entirely with an application focus, with the objective of strengthening the project management skills of students and the use of technological tools, with special emphasis on the alignment of projects to objectives and organizational strategies. During the Project Management Workshop the processes for the initiation, planning, execution, monitoring and control, and project closing will be developed by applying tools and techniques during the project cycle of life. The course contributes to the development of general skills, information management in level 2, as well as specific competence of ABET 2 an ability to apply engineering design to produce solutions that meet specified needs with consideration of public health, safety, and welfare, as well as global, cultural, social, environmental, and economic factors, in Level 2. The course has a prerequisite IS221- project management course. ABET Accreditation Board for Engineering and Technology